New Insights Into the Pathogenesis of Alzheimer's Disease - Fan, Liyuan; Mao, Chengyuan; Hu, Xinchao; Zhang, Shuo; Yang, Zhihua; Hu, Zhengwei; Sun, Huifang; Fan, Yu; Dong, Yali; Yang, Jing; Shi, Changhe; Xu, Yuming (Frontiers in Neurology, 2020)
Alzheimer's disease (AD), a common neurodegenerative disease in the elderly and the most prevalent cause of dementia, is characterized by progressive cognitive impairment. The prevalence of AD continues to increase worldwide, becoming a great healthcare challenge of the 21st century. In the more than 110 years since AD was discovered, many related pathogenic mechanisms have been proposed and the most recognized hypotheses are the amyloid and tau hypotheses. However, almost all clinical trials targeting these mechanisms have not identified any effective methods to treat AD. Scientists are gradually moving away from the simple assumption, as proposed in the original amyloid hypothesis, to new theories of pathogenesis, including gamma oscillations, prion transmission, cerebral vasoconstriction, growth hormone secretagogue receptor 1 (GHSR1) mediated mechanism, and infection. To place these findings in context, we first reviewed the neuropathology of AD and further discuss new insights in the pathogenesis of AD.